Religious Moderation in the Life of Sisya Pasraman Sad Dharma Dwijendra: Response and Its Application in Character Building - Wiguna, Ida Bagus Alit Arta; Ratnaya, I Gede; Badani, ABD Quddus Al (Institut Agama Hindu Negeri Gde Pudja Mataram, 2026)
This study examines the application of the values of religious moderation in the daily life of Sisya Pasraman Sad Dharma Dwijendra and its impact on the formation of their character. The primary focus of the research is on how religious moderation is integrated into non-formal Hindu religious education and its role in shaping the attitudes of tolerance and social harmony among the Sisya. This study employs a case study design with a purposive sampling technique, involving seven Sisya who were selected for semi-structured interviews and supported by direct observation. The research findings show that, although Sisya has demonstrated high tolerance and discipline in worship, there are challenges related to teaching delays that hinder the optimization of religious moderation education. This article contributes to the development of a character education model based on religious moderation in non-formal educational institutions. The results of this study underscore the importance of improving teaching methods and Sisya's involvement in social activities to support the application of more effective religious moderation in character building.